Autistic phenomena in The Adventures of Pinocchio. Issue 2 (April 2017) - Smith, Adrian
Abstract: This paper seeks to demonstrate that the protagonist of Carlo Collodi's The Adventures of Pinocchio illustrates numerous autistic phenomena such as communication difficulties, sensory and perceptual distortions and mindblindness. While Pinocchio is viewed as a literary construct with contraindications of autism, it will be argued that his autistic traits are sufficient to suggest the possibility that Collodi had a partial intuition of the syndrome 60 years before it was identified by Leo Kanner. Approaching Collodi's text in this manner is taken as an opportunity to survey and reflect upon the psychoanalytic literature on autism and to position it in relation to contemporary theories from cognitive neuroscience.